“Diseño de un secador por aire caliente para hojuelas de platano” - Gil Rios, Darvin (2006)
This investigation denominated "Design of a Hot-Air Dryer for Banana Chips" aims to design a dryer with trays crossed by air circulation, with a loading capacity of 500 kilograms of fresh banana chips. Various tests hove been developed in arder to determine the necessary parametérs which hove provided the measures of the equipment, using for this two experimental dryers described in the appendix. The main evaluated parameters using for desing indicated the apparent density of the fresh banana chips with value of 531,73 kg/m3; this misture the end of dryer was of 10,45 3; the properties of the air at different process temperatures was olso, and also of the environment (see pictures Nº 12 and 13); for hot air usig styrax firewood (Myroxylon balsamum} which was also the caloric equivalent to 7 141,47 kcal/kg, and its residual carbon has 6 67 4, 98 kcal/kg; the air velocity of the process was also determined and the value was 4.4 meter for second. The experimental values of drying kinetics (see figures Nº 1 O and 13) and the use of software instruments allowed to know which facilitated to get the measures for a commercial dimensioned dryer. Thus, the required air flow reaches a value of 2 046,50 m3/hr; the total thermal charge was 79 946,60 kcal/hr or 92,96 kw/hr considering a operations security equivalent to two on the net thermal charge, which needs to administer 11, 19 kilograms of firewood per hour of constant operation. For his part, the transfer orea of the interchanger was equivalent to 7 ,24 m2 in the predetermined operation conditions and with the characteristics of the materials the equipment is produced of (indicated in appendix Nº 3). Finally, the cost for the production of the design amounts to S/. 9 883,62 (US $ 2 995,04), excluding the costs for advising and supervision.